Beef cattle welfare assessment: use of resource and animal-based indicators, blood parameters and hair 20β-dihydrocortisol. Issue 1 (14th December 2020) - Tarantola, Martina; Biasato, Ilaria; Biasibetti, Elena; Biagini, Davide; Capra, Pierluigi; Guarda, Franco; Leporati, Marta; Malfatto, Vanda; Cavallarin, Laura; Miniscalco, Barbara; Mioletti, Silvia; Vincenti, Marco; et al.
Abstract: The present study aims to evaluate beef cattle welfare with an integrated approach as housing conditions and management practices change and to investigate the relationship between the adopted parameters and their applicability. A total of 15 Piemontese breed bulls reared in a tied stall housing system and 15 Piemontese, 15 Blonde d'Aquitaine and 15 cross-breed from Ireland reared in group-pen were considered. A welfare protocol including a checklist and the 'RIBECA' scoring system was prepared for the assessment of animal-based measures and resource-based measures. Blood parameters and hair 20β-dihydrocortisol were also analysed. The animal-based score was not significantly different among the farms, while the total welfare score was 'poor' for the animals in the tied stall system, 'fair' for Piemontese cattle in the in pen and Irish cross-breed, and 'very good' for the Blonde d'Aquitaine cattle. Irish cross-breed were the most fearful, with the blood findings also suggesting that these animals showed the worst adaptation, whereas Blonde d'Aquitaine cattle were well adapted. Furthermore, 20β-dihydrocortisol was lower ( p < .01) in Blonde d'Aquitaine cattle when compared to Piemontese cattle tied and Irish cross-breed. The concordance between haematochemical and hair 20β-dihydrocortisol findings observed in the present study suggests that Blonde d'Aquitaine and Piemontese cattle reared in pens were less stressed during their livestock life. Measurements of cortisol metabolites in the hair matrix seem to be a valid diagnostic tool for monitoring animal exposure to situations capable of increasing cortisol levels over time. Highlights: Husbandry and management conditions could negatively affect animal welfare. The RIBECA protocol adopted identified some beef cattle welfare critical points. Checking of different blood parameters and hair cortisol metabolites may integrate welfare assessment.